The Age, parity and stage of cervical cancer among cervical cancer patients attending oncology department- An observational cross sectional study - Hashmat, Sana; Bhutto, Sorath; Haider, Ghulam; QAZI, SHAYAN ALI; shah, amra; Qureshi, Areeba (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
Cervical cancer is one of the common cancers in women worldwide. This study was conducted to determine age, parity and stage of cervical cancer patients in Pakistani population. This was a prospective cross-sectional study, conducted in the Oncology Department of Jinnah Postgraduate Medical Center, Karachi during October 2023 to January 2024. A total of 92 women of age 18 years or above, presenting with biopsy proven cervical cancer were recruited. The mean age of study participants was 53.4 years SD± 10.9 years. The highest proportion of cases were recorded between 47 to 57 years of age with a proportion of 37.0% (n=34). Among the study participants 62% (n=57) had a history of multiparty with at least five or more children and 65% (n=60) were postmenopausal women, while 59.8% (n=55) were found to have Stage-II and Stage-III disease at the time of diagnosis. Histopathologically Squamous Cell Carcinoma was the most frequent histopathological type reported. In conclusion the highest burden of cervical cancer was found to be present among the women of age group 47 to 57 years. Cervical cancer was most prevalent among women with higher parity or having five or more children. Squamous cell carcinoma was the most frequently occurring histopathological type, while most patients were diagnosed at the stage-II disease.